Ecological uncertainty, adaptation, and mitigation in the U.S. ski resort industry: Managing resource dependence and institutional pressures - Tashman, Pete; Rivera, Jorge (Strategic Management Journal, 2016)
We draw on resource dependence and institutional theories to study how firms manage uncertainty in nature (ecological uncertainty) in the U.S. ski resort industry. Through resource dependence theory, we develop the concept of ecological uncertainty and explain its effects on firms' access to and management of natural resources. We then predict that firms adapt to ecological uncertainty with natural‐resource‐intensive practices, as well as practices that attempt to mitigate its underlying causes. Using institutional theory, we also predict that environmental expectations moderate these responses. Our results indicate that firms did manage ecological uncertainty by adopting natural‐resource‐intensive practices, but not mitigation practices. They also show that stronger environmental expectations constrained firms from adopting natural‐resource‐intensive practices and promoted their adoption of mitigation practices in response to ecological uncertainty. Copyright © 2015 John Wiley & Sons, Ltd.